Modeling and simulation of photofabrication processes using unsaturated polyester resins - Matias, João Manuel (2009)
Several kinetic models have been proposed to simulate thermosetting cure reactions. The most complex models, based on a mechanistic approach of cure reactions, are developed based on the concepts of free radical polymerization and the mechanism of reactions with diffusion. However, mechanistic models are usually quite impractical for engineering purposes because of the difficulty in obtaining the model parameters. An alternative to these mechanistic models are the phenomenological models, formulated in terms of the degree of cure and much easier to apply. Phenomenological models have been largely used to study thermal-initiated cure reactions, although only few works used them to model the kinetics of ultraviolet-initiated cure reaction. This work proposes a photo-thermal-kinetic model to study the behavior of unsaturated polyester resins during ultraviolet-initiated cure reactions. The model considers samples with different amounts of initiator concentration and cure reactions performed under different ultraviolet light intensities. The model has been numerically solved using the finite element technique